Psychological Warfare - Linebarger, Paul M. A. (Infantry journal press, 1948)
Psychological Warfare was first published in 1948, and it became the authoritative text on the subject for decades. Even today, it explains the basic principles of propaganda and psychological warfare (both white and black), from organization and planning to analysis and response. Examples are drawn from military history, with an emphasis on tactics by both the Allies and Axis during World War II. This is a fascinating subject, with greater relevance to everyday business and politics than may be immediately recognized.